Effects of physical exercise on male reproductive health - Nesello, Leonardo Monteiro; Pasqualotto, Fábio Firmbach (Seven Editora, 2024)
Regular physical exercise seems to have a positive impact on seminal parameters. However, performing intense activities can lead to significant changes in these parameters. This aspect is particularly relevant given that an increasing number of people around the world are engaged in physical activity. In addition, the rate of marital infertility ranges from 8% to 10%, with up to 50% of cases attributed to male factors. Given this scenario, the study in question conducted a comprehensive analysis of the current literature to investigate the impact of physical activity on male reproductive health. A systematic review was conducted using the PRISMA guidelines for searching, selecting, and extracting data from PubMed databases. A total of 261 articles were identified, of which 13 were selected according to the established flowchart. Based on substantial clinical evidence, this review suggests that intense physical activity can induce significant hormonal changes and negatively affect seminal quality. In contrast, regular exercise appears to have a neutral or even beneficial effect. In addition, the impact of physical activity on semen quality can vary depending on the type of exercise performed. Despite these observations, there is still a lack of consensus on the subject, due to the contradictions between studies and the difficulty in quantifying physical activity precisely. DOI:https://doi.org/10.56238/sevened2024.025-004